Phenotypic Analysis of a Case of “3MC Syndrome” with Review of Literature - Rani Roy, Soma; Md. Sazzad Kader, Md. Sazzad Kader (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
3MC syndrome is a very rare entity. It’s prevalence is unknown but most cases are reported from Middle East. First case was reported in 1978 and named as Michel syndrome and recently with other three syndromes together these syndromes are named as 3 MC syndrome. All are autosomal recessive disorder and reported from both consanguineous and non-consanguineous parents. Here we phenotypically analyzed a case presented with the features of blepharophimosis syndrome associated with craniosynostosis suggestive of Mischel syndrome which is a part of ‘3 MC syndrome’